Implementasi Metode Agile Scrum Dalam Perancangan UI/UX Design Command Control Map Service Di PT. Len Industri (Persero) - Sholehah, Ragil Siti; Fauzi , Ahmad; Majid, Nuur Wachid Abdul (JURNAL FASILKOM, 2024)
The rapid development of technology will create various advancements in digital product development across various life sectors. One of them is the design of UI/UX, which is the interface of a product that interacts directly with users. This is important to produce products that are suitable and satisfying for users. The UI/UX Design Command Control Map Service design uses the Agile Scrum method, with the principle of team collaboration. The research aims to examine how the scrum method is applied, its influence on improving design quality, and the responsibility and collaboration of each team member. Project management needs to use appropriate methods to produce results that are effective and timely. Agile Scrum employs an adaptive and collaborative approach. The product design process follows stages starting from the product backlog, sprint backlog, sprint planning, sprint review, and sprint retrospective. Collaboration among team members, including the product owner, scrum master, and developers, is key. The design results of the system interface using the Agile Scrum method are suitable because they meet user needs and can quickly address issues due to the ability to accept changes in the design process with effective stakeholder communication using Agile Scrum in UI/UX Design Command Control Map Service. Interviews with team members concluded that the Agile Scrum method used in design helps prioritize work tasks for team members and the stages of scrum aid in communication and collaboration among team members. In this study, the Agile Scrum method was only applied to one project, so a suggestion for further research is to investigate the implementation of the Agile Scrum method in various projects and environments to comprehensively evaluate its effectiveness.